Forced sex and its predictors among students attending university: a cross-sectional study - Shayesteh Jahanfar; Parivash Ahmadpour; Mojgan Mirghafourvand (BMC, 2022)
Abstract Background Forced sex is associated with negative psychological health outcomes. This study aimed to determine the prevalence of forced sex and its predictors. Methods This cross-sectional study was performed on 800 students of a university in USA using a random sampling method. Reproductive health electronic questionnaire was used for data collection. Due to the sensitive nature of the questionnaires and for anonymity, Qualtrics software was used. To estimate the extent of the effect of each of the independent variables (knowledge, attitude, as well as socio-demographic characteristics) on the dependent variable (forced sex), multivariate logistic regression was used. Results About one-fifth of students (16.9%) had experienced forced sex. The variables of gender, knowledge about sexually transmitted diseases (STD), and sexual attitude were among the predictors of forced sex. This kind of sexual relationship was more likely to occur in girls than in boys (OR = 2.94, 95%CI: 1.20 to 1.71). Further, the chance of forced sex significantly increased with growing knowledge of STD (OR = 1.41, 95%CI: 1.61 to 1.71), and sexual attitude (OR = 1.23, 95%CI: 1.04 to 1.21). Conclusion Considering the impact of gender, knowledge about STD, and sexual attitude on forced sex, educational interventions among the youth especially girls are required to provide complete and proper information about sexual and reproductive health and rights and correct the sexual attitudes of the youth.